1994
DOI: 10.1136/bjo.78.6.461
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ocular blood flow during increases of arterial blood pressure.

Abstract: The blood flow in the uvea in cats and monkeys during acute increases of arterial blood pressure is well controlied by a sympathetic mechanism protecting the eye from overperfusion. Ocular macrocirculation (ophthalmic artery) and ocular microcirculation (iris) were examined in 22 healthy subjects during acute increases of arterial blood pressure induced by physical exercise (125 W). With a data aquisition and storage software in real time mode several parameters of ocular perfusion and systemic functions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 8 publications
2
18
1
1
Order By: Relevance
“…Em humanos observou-se que a PAM elevada não alterava a Po, pois ocorria aumento na resistência vascular e a velocidade média de fluxo sangüíneo permanecia constante na arté-ria oftálmica e nas artérias ciliares (19) . Em suínos relata-se que a hipotensão arterial induzida por drogas não alterava a Po (20) .…”
Section: Discussionunclassified
“…Em humanos observou-se que a PAM elevada não alterava a Po, pois ocorria aumento na resistência vascular e a velocidade média de fluxo sangüíneo permanecia constante na arté-ria oftálmica e nas artérias ciliares (19) . Em suínos relata-se que a hipotensão arterial induzida por drogas não alterava a Po (20) .…”
Section: Discussionunclassified
“…Many studies have shown that choroid flow did not change during exercise because of autoregulation [1,2,3,4,5,6]. In particular the dynamic exercise should increase the flow velocity due to the increase in heart rate and systemic pressure, but theoretically local regulation could keep ocular flow at the same level or decrease the choroid and retinal capillary flow during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The parallel changes of vascular resistance and blood pressure during exercise might be the reason for a constant blood flow in the ophthalmic artery [6]. Some studies have analyzed ocular blood flow after dynamic exercise to understand ocular autoregulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations